2002
DOI: 10.1046/j.1471-6712.2002.00063.x
|View full text |Cite
|
Sign up to set email alerts
|

Colour perception among the very elderly related to visual and cognitive function

Abstract: Colour perception was studied among a representative sample of 95-year olds and compared with previously examined 80-year olds and a group with Alzheimer's disease (AD), mean age of 80 years. The 95-year olds' results were on a significantly lower level than the other two groups but showed a similar pattern as to colour -discrimination, -naming, -preferences and colour/form recognition. Visual function among 95-year olds had only minor influence on their result in contrast to cognitive function which had a mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 22 publications
2
39
0
Order By: Relevance
“…Colour perception was compared in cognitively intact 80 and 95 year old individuals and in participants with AD. 49 Performance of the 95 year olds was poorer than the 80 year olds but similar to the AD participants, overall lower colour perception ability in the 95 year olds being attributable to age rather than any additional factor. In a further study, although the number of participants was small (n = 10), colour deficits identified in AD by L'Anthony D-15 desaturated colour test could be accounted for by age-related changes.…”
Section: Colour Visionmentioning
confidence: 66%
See 1 more Smart Citation
“…Colour perception was compared in cognitively intact 80 and 95 year old individuals and in participants with AD. 49 Performance of the 95 year olds was poorer than the 80 year olds but similar to the AD participants, overall lower colour perception ability in the 95 year olds being attributable to age rather than any additional factor. In a further study, although the number of participants was small (n = 10), colour deficits identified in AD by L'Anthony D-15 desaturated colour test could be accounted for by age-related changes.…”
Section: Colour Visionmentioning
confidence: 66%
“…Hence, the effectiveness of some of these methods in testing participants especially those with severe dementia should be taken into account. Fourth, participants may have been visually assessed without having had an eye examination, and thus, without knowing if the optimal Controversial but likely to be affected in AD, DLB and PDD [47][48][49][50][51][52][53] Stereoacuity Impaired in AD and VD 41,[54][55][56] Contrast sensitivity Impaired in AD and VD [59][60][61][62] Motion detection…”
Section: Visual Dysfunction In Dementiamentioning
confidence: 99%
“…Previous studies have reported contradictory results; some authors found no differences between AD patients and controls [25] , while others found reduced color discrimination capacity in AD patients which was unrelated to the severity of dementia [26,27] . In the current study, patients with mild to moderate AD were compared with control subjects of the same age.…”
Section: Discussionmentioning
confidence: 88%
“…The lens darkens and yellows, blocking short wavelength light, so blues appear darker, and patients can struggle to differentiate colors that differ only in their blue content. Primary colors are best, with reds and yellows being the easiest to discern [32]. For these reasons, we used white for the background color with answer option buttons in red, navigational buttons in green, and pause and stop buttons in yellow (Fig.…”
Section: Methodsmentioning
confidence: 99%